1997
DOI: 10.1111/j.1751-1097.1997.tb01894.x
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Localization of Photofrin and Aminolevulinic Acid and Photodynamic Cross‐Resistance in Vitro in Radiation‐Induced Fibrosarcoma Cells Sensitive or Resistant to Photofrin‐Mediated Photodynamic Therapy

Abstract: The subcellular and, specifically, mitochondrial localization of the photodynamic sensitizers Photofrin and aminolevulinic acid (ALA)-induced protoporphyrin-IX (PpIX) has been investigated in vitro in radiation-induced fibrosarcoma (RIF) tumor cells. Comparisons were made of parental RIF-1 cells and cells (RIF-8A) in which resistance to Photofrin-mediated photodynamic therapy (PDT) had been induced. The effect on the uptake kinetics of Photofrin of coincubation with one of the mitochondria-specific probes 10N-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
103
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(114 citation statements)
references
References 35 publications
10
103
0
1
Order By: Relevance
“…In addition, the 1 O 2 luminescence signal was undoubtedly heterogeneous in origin in that, for example, the photosensitiser was likely concentrated in specific tissue and/or cellular compartments (e.g. mitochondrial membrane; Wilson et al, 1997b) and the oxygenation is higher in membranes than in cytosol. However, the proportion of radiative vs nonradiative 1 O 2 was consistent between experiments, since we used the same photosensitiser and application conditions in all cases.…”
Section: Singlet Oxygen As An In Vivo Dose Metricmentioning
confidence: 99%
“…In addition, the 1 O 2 luminescence signal was undoubtedly heterogeneous in origin in that, for example, the photosensitiser was likely concentrated in specific tissue and/or cellular compartments (e.g. mitochondrial membrane; Wilson et al, 1997b) and the oxygenation is higher in membranes than in cytosol. However, the proportion of radiative vs nonradiative 1 O 2 was consistent between experiments, since we used the same photosensitiser and application conditions in all cases.…”
Section: Singlet Oxygen As An In Vivo Dose Metricmentioning
confidence: 99%
“…The presence of competitive binding agents can also in-°u ence the subcellular localization and/or binding of PSs. 7 As one can expect, the presence of prooxidant factors in cancer cells might scavenge PDT-induced oxygen species and therefore have a negative e®ect on PDT e±cacy. 8 Great variations in PS uptake can be found between individual cell lines, resulting in even more pronounced di®erences in photocytotoxicity.…”
Section: Mode Of Actionsmentioning
confidence: 99%
“…30,31 Early studies also suggested that the intra and extracellular PpIX accumulation mediated by ALA were not subjected to the level of P-gp expression, 32 but the rapid e®lux of PpIX had also been demonstrated in DT-resistant variants. 7 Savitskiy et al showed that the speci¯c cellular protein P-gp 170 did not appear to alter the intracellular accumulation of chlorins. 33 Later Saczko et al showed that P-gp appeared to play a role in the intracellular accumulation of Photofrin but not hypericin in doxorubicin-resistant human colon cancer cell lines (LoVo cells).…”
Section: P-gp and Ps Uptakementioning
confidence: 99%
“…NAO has also been used to reveal properties of the binding of photosensitizers in cultured cells. Wilson et al (Wilson et al, 1997) found that NAO competitively inhibited the uptake of Photofrin® into mitochondria, indicating that some photosensitizers might bind to CL of the inner mitochondrial membrane. Pc 4, a phthalocyanine photosensitizer first synthesized at Case Western Reserve University and now in clinical trial at University Hospitals Case Medical Center, was reported to be localized near CL based on fluorescence resonance energy transfer (FRET) from NAO to Pc 4 (Morris et al, 2003).…”
Section: Introductionmentioning
confidence: 99%